The Effect of De Bono Model on Students’ Achievement in Writing Descriptive Text of 2018/2019 Eleventh Year Students of SMA Yayasan Pendidikan Harapan Bangsa Kuala Kabupaten Langkat - Conny Conny; Aginta Endingna Sembiring (STKIP Budidaya Binjai, 2018)
The study is concerning with experimental study which discussed the effect of de Bono model students writing descriptive text. It took place at SMA yayasan pendidikan harapan bangsa kuala kabupaten langkat. The subjects were the eleventh year students with the population of 72 students. 72 students were chosen as the sample and group into experimental and control group. Each group consisted of 36 students. The experimental group was taught with de bono model while the control one was taught without De bono model. A writing test was used to collect the data on the students’ writing achievement. The data collected were analyzed by using t-test. The result of the data analysis showed that the t-observed was 7,24. It was higher that the value of t-table (tt) is 1,66 for 5% and 2,38 for 1%. This meant that the alternative hypothesis (Ha) was accepted. It can be concluded that there is effect of De Bono model on students writing descriptive text of 2018/2019 eleventh year students of SMA yayasan pendidikan harapan bangsa kuala kabupaten langkat.Keyword: Writing, Descriptive text, De Bono model, Six thinking hats